Evaluation of the Reasons for the Cancellation of Elective Procedures at Level 3 University Hospital on the Day of Surgery - Altun, Aysun Yildiz; Ozer, Ayse Belin; Aksoku, Berna Turhan; Karatepe, Umit; Kilinc, Mikail; Erhan, Omer Lutfi; Bolat, Esef (Elsevier Science Inc, 2020)
Purpose: Unexpected cancellations of planned elective procedures are a global problem for hospitals, causing a waste of hospital resources and manpower, and reduces the efficiency of hospitals. In this study, we tried to identify the causes of cancellations of elective procedures, and to examine the relationship between the causes. Design: A retrospective, descriptive single-center study. Methods: Nine thousand five hundred sixty-six elective procedures scheduled between January 2015 and December 2015 were retrospectively examined. Reasons for cancellation, the associated surgical clinic, and the day and season of the canceled procedures were recorded. Findings: Of the total 9,566 procedures, 496 (5.2%) were canceled. Of the cancellations, 31.3% were due to patient-related reasons, 29.2% because of inadequate anesthesia preparation, and 19% because of nonavailability of operating rooms. Conclusions: Cancellation of elective surgeries causes a waste of time and resources. Determining the reasons for cancellations to reduce cancellation rates is important for each hospital. (c) 2020 American Society of PeriAnesthesia Nurses. Published by Elsevier, Inc. All rights reserved.
Keywords: surgery cancellations; frequency of cancellations; reasons for cancellations